STRATEGI BIMBINGAN MANASIK IBADAH HAJI PADA KBIH NURUSSALAM LAMPUNG TIMUR - Zakky Fakhril Amin (Institut Agama Islam Negeri Metro, 2021)
The purpose of this study was to determine the guidance strategy of the pilgrimage rituals in the form of fulfilling the needs of pilgrims in terms of increasing knowledge of pilgrims about the pilgrimage at KBIH Nurussalam East Lampung. The method used is qualitative and has descriptive characteristics. The results concluded that the Hajj rituals guidance strategy at KBIH Nurusssalam East Lampung was quite good, this was seen in meeting the needs of pilgrims' understanding of the pilgrimage such as providing guidance on Hajj rituals with methods and modules that were quite good and explained by competent speakers so that the material could be used. well absorbed by prospective pilgrims at KBIH Nurusssalam East Lampung